2010
DOI: 10.1111/j.1365-2745.2010.01652.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant survival in relation to seed size along environmental gradients: a long‐term study from semi‐arid and Mediterranean annual plant communities

Abstract: Summary 1.A positive relationship between seed size and subsequent offspring survival is a key assumption in ecological theory concerning life-history strategies. Yet, this relationship is uncertain in respect to lifetime survival because sound evidence only exists for early seedling stages. Furthermore, the effect of environmental variation in space and time, and of contrasting plant functional groups, on this relationship has been scarcely examined. 2. Here, we investigated survival and between-year variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
135
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 55 publications
7
135
1
4
Order By: Relevance
“…However, our results also indicated that the influence of SM on seedling biomass differed between the seeds collected in the two maternal environments, with a strong and steeper seed-to-seedling biomass relationship for seeds from the stressful environment (Figure 3). That the benefits of heavier seeds are higher under stressful conditions have been demonstrated for different plant species (Metz et al, 2010), but the key finding of our analyses is that the seed-to-seedling relationship was determined by the maternal environment rather than by the environmental conditions where the seeds are grown, which, in our study, were similar for all seedlings. Two non-exclusive mechanisms may explain these results.…”
Section: Maternal Environmental Effects On Sm Variabilitymentioning
confidence: 50%
See 1 more Smart Citation
“…However, our results also indicated that the influence of SM on seedling biomass differed between the seeds collected in the two maternal environments, with a strong and steeper seed-to-seedling biomass relationship for seeds from the stressful environment (Figure 3). That the benefits of heavier seeds are higher under stressful conditions have been demonstrated for different plant species (Metz et al, 2010), but the key finding of our analyses is that the seed-to-seedling relationship was determined by the maternal environment rather than by the environmental conditions where the seeds are grown, which, in our study, were similar for all seedlings. Two non-exclusive mechanisms may explain these results.…”
Section: Maternal Environmental Effects On Sm Variabilitymentioning
confidence: 50%
“…Environmental conditions and resource availability may determine the amount of resources that the mother plants allocate to the developing seeds, which, in turn, may affect seed mass (SM), thus shaping many traits in seedling establishment and early growth, especially, under stressful and competitive conditions (Castro et al, 2006;Metz et al, 2010). SM may be, thus, simply passively determined by the available resources in the maternal environment, where impoverished conditions lead to reduced SM, and thus, reduced seedling performance.…”
Section: Introductionmentioning
confidence: 99%
“…Df=degrees of freedom Previous empirical observations have demonstrated the benefits of yielding bigger seeds under stressful environments (e.g. Metz et al 2010;Moles and Westoby 2004;Stock et al 1990;Violle et al 2009;Zas et al 2013). Favouring seeds as heavy as possible to the detriment of a higher number of light seeds allows the plant to develop bigger embryos with greater vitality and amount of reserves (Delgado et al 2001) and to give rise to more vigorous seedlings with lower mortality rate (Castro 1999;Escudero et al 2000;Moles and Westoby 2004;Reyes and Casal 2001; but see Moles and Westoby 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lower establishment success in I. rubriflora might be related to the production of seedlings with proportionally fewer reserves that are therefore less likely to survive adverse conditions such as herbivory, or that have a less developed root system (Leishman et al, 2000). However, this recruitment advantage of the widespread I. purpurea may be temporary and may not carry through to the adult phase in accordance with the hypotheses of a temporal advantage of large-seeded species due to proportionally higher reserves (Moles and Westoby, 2006; but see Metz et al, 2010). Herbivory on adult plants of I. purpurea can be high at the study regioneup to 90 percent of leaf areaewhile adult plants of I. rubriflora are rarely attacked (J. Astegiano, personal observation) and this may explain the lower (though not significantly so) transition probability to the reproductive adult phase in this geographically widespread species.…”
Section: Discussionmentioning
confidence: 55%
“…Thus survival in these life-history stages may differ between species with contrasting seed masses (Leishman et al, 2000). However, this advantage of larger-seeded species may be temporary and disappear in subsequent life-history stages (Moles and Westoby, 2006; but see Metz et al, 2010). On the other hand, in species reaching higher seedling densities due to higher seed production or seedling establishment success, processes like intra-specific competition or herbivory could be enhanced resulting in a decrease in the number of plants becoming reproductive adults (Harms et al, 2000;Goldberg et al, 2001;Maron and Crone, 2006).…”
Section: Introductionmentioning
confidence: 99%